2014
DOI: 10.1016/j.geoforum.2013.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Household vulnerability in rural areas: Results of an index applied during a housing crash, economic crisis and under austerity conditions

Abstract: Publication informationGeoforum, 51 : 75-86 Publisher ElsevierItem record/more information http://hdl.handle.net/10197/5026 Publisher's statement þÿ T h i s i s t h e a u t h o r s v e r s i o n o f a w o r k t h a t w a s a c c e p t e d f o r p u b l i c a t i o n i n G e o f o r u m .Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this document. Changes may have been made to this wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 45 publications
1
27
0
1
Order By: Relevance
“…Vulnerability research, as a new paradigm of sustainable development, uncertainty and risk, sheds light on how to best analyze the uncertainty of innovation capability. As an innovative method, SPA focuses on uncertainty and is widely applied in the economic and social fields [11,12,18,26,[111][112][113][114], and is combined with some common comprehensive methods, such as E-SPA and P-SPA [44,[100][101][102]. Innovation capability is an important driver of economic development and is closely linked to uncertainty and risk.…”
Section: Discussionmentioning
confidence: 99%
“…Vulnerability research, as a new paradigm of sustainable development, uncertainty and risk, sheds light on how to best analyze the uncertainty of innovation capability. As an innovative method, SPA focuses on uncertainty and is widely applied in the economic and social fields [11,12,18,26,[111][112][113][114], and is combined with some common comprehensive methods, such as E-SPA and P-SPA [44,[100][101][102]. Innovation capability is an important driver of economic development and is closely linked to uncertainty and risk.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, it is difficult to describe the characteristics of social vulnerability if there were only few indicators, but on the other hand, if too many indicators were selected and used, there were also some problems, such as inaccessible data, complex calculation and poor operability (Cutter et al, 2003;Murphy and Scott, 2014). It is important that the selected indicators are in a manageable level, for which the PCA is a good method to use (Liu et al, 2013).…”
Section: Key Problems In Using Index-based Assessment Methodsmentioning
confidence: 99%
“…In order to effectively reduce the adverse effects of a flood disaster, it is necessary to enhance the understanding of the social vulnerability of flood-hazard-prone areas (Cutter et al, 2003Zhang and You, 2014). Since Cutter developed a social vulnerability index to measure the social vulnerability to environmental hazards (Cutter et al, 2003), there has been growing concern and interest in this area (Bjarnadottir et al, 2011;Noriega and Ludwig, 2012;Zebardast, 2013;Siagian et al, 2014;Garbutt et al, 2015). For example, Noriega and Ludwig (2012) assessed the social vulnerability to local earthquake risk in Los Angeles County, California, United States, and they found that "knowledge of the relationship between earthquake hazard and the demographic characteristics of people in the area at risk is essential to mitigate the local impact from earthquakes".…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, although there is a substantial literature on the role of discourses in (re)producing the neoliberal politics of crisis and austerity (see for instance Fairclough 2013;Blyth 2013;Schmidt 2016), this has tended to leave untouched the question of how the household might be implicated in such discourses. This is not to say that the household is overlooked per se, for scholars have explored both the housing market as a cause of crisis and the consequences of austerity on households (see for instance Hay 2011;Browne 2012;Murphy and Scott 2014;O'Hara 2015). Yet the household as a discursive site in and of itself does not tend to feature in discussions of crisis and austerity.…”
Section: Politicising Discourses Of Household Wastementioning
confidence: 99%